Os desenhos da cidade observada: uma reflexão singular - Oliveira, Alexandre Suarez de [UNESP]; Tamai, Sidney [UNESP] (My University, 2014)
How are teachers Cartoons observation Architecture Schools in several decades, the idea was to try and explain firsthand the look and fundamental elements of drawings to the Architect. We start looking through the design of: 1 A projective gaze: the invisible is made visible by interactivity and space and time are perceived by the distance that look place between them; 2nd In bidirectional contamination: the object fills the subject, double-hand, bringing the tactile qualities of architecture in continuous resonance, 3rd Strangeness by slow look: draw as perceptual expansion strategy; 4 Articulation of the structural elements of the design while similar language to architecture and city through the selection of appropriate signs and codes, exclusive and singular.
Keywords: Design; City; Architecture; Art